2022
DOI: 10.3390/cancers14143485
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analysis of Serial 18F-fluciclovine PET-CT and Multiparametric MRI during Chemoradiation for Glioblastoma

Abstract: Anti-1-amino-3-18fluorine-fluorocyclobutane-1-carboxylic acid (18F-fluciclovine) positron emission tomography (PET) shows preferential glioma uptake but there is little data on how uptake correlates with post-contrast T1-weighted (Gd-T1) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) activity during adjuvant treatment. This pilot study aimed to compare 18F-fluciclovine PET, DCE-MRI and Gd-T1 in patients undergoing chemoradiotherapy for glioblastoma (GBM), and in a parallel pre-clinical GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, sensitivity achieved 100% when [ 18 F]FACBC PET and MRI were combined [20]. In our review, tumor volumes defined by [ 18 F]FACBC uptake, were significantly larger than those defined by contrast-enhanced MRI [19][20][21]26,27]. On the other hand, only Michaud et al [22] showed a substantial volume overlap between [ 18 F]FACBC and MRI.…”
Section: Results Of Qualitative Analysismentioning
confidence: 59%
See 4 more Smart Citations
“…However, sensitivity achieved 100% when [ 18 F]FACBC PET and MRI were combined [20]. In our review, tumor volumes defined by [ 18 F]FACBC uptake, were significantly larger than those defined by contrast-enhanced MRI [19][20][21]26,27]. On the other hand, only Michaud et al [22] showed a substantial volume overlap between [ 18 F]FACBC and MRI.…”
Section: Results Of Qualitative Analysismentioning
confidence: 59%
“…Only one study showed a correlation between areas of tumor proliferation (i.e., Ki-67) by immunohistochemistry staining and amino acid transporter in a pre-clinical model, suggesting that uptake occurred in biologically active tumors [19].…”
Section: Results Of Qualitative Analysismentioning
confidence: 99%
See 3 more Smart Citations